Design and Development of Real - Time Blood Bank Interface using MERN Stack - R, Dileep. M; Bhat, Shama; Shukur, Mohamed Ghouse; V, Navaneeth. A; D, Vidya Sagar. S; Rallapalli, Sreekanth (2025 International Conference on Intelligent Computing and Knowledge Extraction (ICICKE), 2025)
The goal of the "Real-Time Application for Blood Bank Using MERN Stack" is to use contemporary web Technologies to overcome the difficulties that conventional blood banks encounter. Making an effective and scalable platform that enables real-time communication between administrators, recipients, and donors of blood is the main goal of the project. The application, which is based on the MERN (MongoDB, Express, React, and Node) stack, combines a responsive frontend with reliable backend services to assure a smooth user experience across platforms. The system makes use of Node.js for effective server-side operations, Express.js. For fast API development, React.js for dynamic and interactive user interfaces, and MongoDB for flexible data storage. The project addresses the critical need for a centralized, accessible, and responsive blood donation management system, ensuring that blood banks can effectively manage inventory, respond to emergencies promptly, and engage with the community in real-time.